Iodine-responsive poly (HEMA–PVP) hydrogel for self-regulating burst-free extended release. Issue 5 (24th March 2017) - Xu, Jinku; Zhao, Peili; Zhang, Yongchun
Abstract: Swollen hydrogels with extended iodine release kinetics is highly desirable for burn and scald treatment. In this paper semi-interpenetrating poly (HEMA–PVP) hydrogels were prepared by radical polymerization followed by thermo-treatment to crosslink its PVP component. Incorporation of PVP component endows the hydrogels responsive to loaded iodine undergoing a reversible shrunken/swollen volume transition. This resulted in a self-regulating iodine release model, in which shrunken hydrogel at high iodine loading decreased drug diffusion thereby reducing burst release, and then gradually swollen hydrogel as drug release ensures rapid release of dissociated drug from strong affinity sites on hydrogel backbone, achieving a burst-free extended release. The hydrogels demonstrated 11.5-fold higher iodine loading than pure pHEMA hydrogel and showed a highest 40% volume shrink. Initial burst release of iodine was efficiently decreased from 12, 894 μg/day of pure pHEMA hydrogel to 2570 μg/day of pHEMA/PVP hydrogel with 37% PVP content. Iodine-loaded hydrogels showed zero-order release at three time periods of 0–15 h, 15 h–3.5 days and 3.5–23.5 days corresponding to release rate of 2570, 776 and 493 μg/day. The work gained a new insight into swollen hydrogel drug delivery system with burst-free extended drug release kinetics.